Síndrome de Evans - presentación atípica de un linfoma raro - Catarina Teles Neto; Marta Valentim; Filipa Pedro; Pedro Luís; Ana Gameiro; Luís Siopa (Sociedade Galega de Medicina Interna, 2022)
Evans Syndrome is a rare autoimmune condition characterized by two or more cytopenias, usually autoimmune haemolytic anaemia and immune thrombocytopenic purpura. It can be primary/idiopathic or secondary to other diseases. Authors describe an Evans syndrome case due to a splenic marginal zone lymphoma, a rare non-Hodgkin lymphoma.